Efektivitas Progressive Muscle Relaxation terhadap Tekanan Darah pada Penyakit Hipertensi - Ricky Zainuddin; Ayu Fransisca Aliwu; Rini Rachmawaty; Yuliana Syam (Universitas STRADA Indonesia, 2018)
Introduction: Progressive Muscle Relaxation is a muscle relaxation technique that does not require imagination, perseverance or suggestion. Muscle relaxation is a skill that can be learned and used to reduce or eliminate tension and stimulate a sense of comfort without being dependent on things / subjects outside of itself. Objectives: reduce pain, reduce blood pressure, reduce anxiety, and reduce stress. Method: this study explores evidence published in electronic data: Pubmed, google scholar. Five studies were included in the last analysis. Results: we were able to see a significant effect in reducing blood pressure in hypertensive disease receiving Progressive Muscle Relaxation compared to the group that did not receive Progressive Muscle Relaxation training. Conclusion: These results show that Progressive Muscle Relaxation can be a non-pharmacological therapy in reducing blood pressure in Hypertension and nurses can participate in providing this training.